Review on the Non-Uniform Frosting/Defrosting Characteristics of Air-Cooled Refrigerator Evaporators - HAN Xudong; ZHANG Xinyi; WANG Han; ZHAO Rijing; HUANG Dong (Zhileng xuebao, 2025)
Non-uniform frost is a significant feature of evaporator surface frost in air-cooled refrigerators, and it is also one of the important causative factors leading to evaporator performance degradation. This paper undertakes a review of the extant research in three distinct areas: firstly, the non-uniform frost characteristics of air-cooled refrigerator evaporators; secondly, defrost optimization based on these characteristics; and thirdly, frost detection optimization. It provides a concise introduction to the formation mechanism of non-uniform frost on air-cooled refrigerator evaporators, the influencing factors and their impact on. The performance of the refrigerator is systematically summarized. The frost-heat-matching defrost optimization and frost suppression strategies based on non-uniform frost are also summarized. The complex challenges and solution ideas of the direct and indirect frost detection techniques under the condition of non-uniform frost are analyzed. Finally, the paper summarizes and discusses the air-cooled refrigerator evaporator performance degradation. Finally, the study identifies shortcomings in the research field of non-uniform frost on the evaporator of air-cooled refrigerators, and puts forward potential future development directions. The aim of this is to provide a framework for efficient operation and energy-saving optimization of air-cooled refrigerators.